In vivo cellular-resolution imaging of retina: modality, cells, and clinical implications - Pi, Shaohua; Brown, Richard; Yun, Samuel; Wang, Lingyun (Frontiers in Ophthalmology, 2026)
The retina, a crucial component of the human eye for vision, is responsible for converting light signals into neural signals that the brain can interpret. It’s a complex tissue, rich in photoreceptors, and supported by various other cell types, including inner nuclear layer cells, ganglion cells, pigmented epithelial cells, immune cells, and vascular cells. Each of these cells plays a vital role in visual processing and understanding of their function and interactions are essential for assessing vision health and diagnosing diseases. Traditionally, studying the retinal cells has relied heavily on histological techniques, which, despite their utility, offer only static images and require invasive procedures that preclude the observation of dynamic biological processes. In this context, recent advancements of in vivo imaging technologies have marked a significant leap forward. Techniques such as ophthalmoscopy, optical coherence tomography (OCT), adaptive optics (AO), two-photon excitation microscopy (TPM), and light-sheet fluorescence microscopy (LSFM) now enable the direct observation of retinal cells in living organisms. This shift from invasive, static methods to dynamic, non-destructive imaging allows for a more nuanced understanding of retinal cell behavior under physiological conditions. It opens up new avenues for the study of the retina’s complex ecosystem in both health and disease, facilitating early diagnosis of retinal conditions and offering new strategies for treatment. By offering a window into the live retina, in vivo imaging stands as a cornerstone of contemporary ophthalmology, promising to enhance our understanding of eye health and to spur innovations in the diagnosis and treatment of ocular diseases.